Analysis of the asphalt paving of the DNIT and the municipality of Gurupi – TO (Research, Society and Development, 2022)
Paving is of very significant importance for the population, in a globalized world it is impossible not to need paved roads to get around. Obviously, in some places there is not always adequate paving, or even any paving, but it is important to understand that a well-structured and well-executed pavement project can bring benefits not only to drivers but to the population as a whole. The main objective of the research is to analyze the asphalt paving of the municipality of Gurupi carried out by the City Hall and the National Department of Infrastructure and Transport between the years 2020 to 2021. The research is classified as documentary and exploratory, with a qualitative approach, since will be collected in the municipality's Transparency Portal and the management reports prepared by the city of Gurupi, in the time period studied. The roads that have the maintenance carried out by the DNIT proved to be of better quality and greater durability in relation to future maintenance, than those that have their maintenance carried out by the City Hall.